RECOMMENDED SISTIM TES KEPRIBADIAN DALAM PEMBENTUKAN KARAKTER DIRI PELAJAR SMA/SMK DENGAN METODE MULTI CRITERIA DECISION MAKING (MCDM) - Aji Sudibyo; Bakhtiar Rifai (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan)
The succes and failure of a person in life both at work, and society much influenced by the attitude and personality traits. Formation and character development must be established as early as possible. Formation and character development is very necessary for high school/vocation high school students who still need brawls between students, skipping school, drugs, pornography, and others. From these questions, we need an expert system about personality test and character development to help high school/vocational students to have knowledge about who they are, so that they have an assessment of the future to go forward to help after graduating from high school/vocational school.